Work-life boundary management of peer support workers when engaging in virtual mental health support during the COVID-19 pandemic: a qualitative case study - Elmira Mirbahaeddin; Samia Chreim (BMC, 2023)
Abstract Background Mental health care needs have increased since the COVID-19 pandemic was declared. Peer support workers (PSWs) and the organizations that employ them have strived to provide services to meet increasing needs. During pandemic lockdowns in Ontario, Canada, these services moved online and were provided by PSWs from their homes. There is paucity of research that examines how providing mental health support by employees working from home influences their work-life boundaries. This research closes the gap by examining experiences of work-life boundary challenges and boundary management strategies of PSWs. Methods A qualitative case study approach was adopted. Interviews with PSWs who held formal, paid positions in a peer support organization were conducted. Data was analyzed thematically using both inductive and deductive approaches. Descriptive coding that closely utilized participants' words was followed by inferential coding that grouped related themes into conceptual categories informed by boundary theory. Member checking was conducted. Results PSWs provided accounts of work-life boundary challenges that we grouped into three categories: temporal (work schedule encroachments, continuous online presence), physical (minimal workspace segregation, co-presence of household members and pets) and task-related (intersecting work-home activities). Strategies used by PSWs to manage the boundaries consisted of segmenting the work-life domains by creating separate timescapes, spaces and tasks; and integrating domains by allowing some permeability between the areas of work and life. Conclusion The findings from this study can help inform management, practices, future research and policy on health care workforce. The study highlights the need to attend to the consequences of greater work-life integration for mental health workers since their successful practice is largely dependent on maintaining self-care. Training regarding work-life boundary management is highlighted as one of the ways to approach situations where work from home is required.